2007
DOI: 10.25077/js.4.1.29-39.2007
|View full text |Cite
|
Sign up to set email alerts
|

EFEK SISA DAN TAMBAHAN TITONIA TERHADAP SIFAT KIMIA ULTISOL DAN HASIL TANAMAN jagung PADA MUSIM TANAM KE TIGA

Abstract: Last researchers reported that Tithonia diversifolia (Mexican sunflower) could replace 25% to 50% of N and K of commercial fertilizer applied in chili production on the first and second planting time in the Ultisols of West Sumatra. A Continuation field experiments was conducted to find out the the appropriate NK cobination sources should be added on the third season to get the higest yield of maize. The treatments were the combination of NK T. diversifolia + NK commercial fertilizer which is maize needed. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Increasing pH value as increasing SOM also reported by [11], in which soil pH increased from 5.86 to 6.03 (in 2007) and from 5.43 to 6.20 (in 2008) by addition of 10 ton manure/ha on Alfisols ( (Oxic tropuldalf) ) in Nigeria. Reference [12] also found that increasing soil pH as OM added to Reiff loam soil (coarse-loamy, mixed, nonacid, thermic Mollic Xerofluvents) and Yolo silt loam soil (finesilty, mixed, nonacid, thermic Typic Xerorthents) in California, USA. During their research, soil pH value consistently increased for 8 years (1988-1996) research.…”
Section: A Soil Cemical Characteristicsmentioning
confidence: 99%
“…Increasing pH value as increasing SOM also reported by [11], in which soil pH increased from 5.86 to 6.03 (in 2007) and from 5.43 to 6.20 (in 2008) by addition of 10 ton manure/ha on Alfisols ( (Oxic tropuldalf) ) in Nigeria. Reference [12] also found that increasing soil pH as OM added to Reiff loam soil (coarse-loamy, mixed, nonacid, thermic Mollic Xerofluvents) and Yolo silt loam soil (finesilty, mixed, nonacid, thermic Typic Xerorthents) in California, USA. During their research, soil pH value consistently increased for 8 years (1988-1996) research.…”
Section: A Soil Cemical Characteristicsmentioning
confidence: 99%
“…From a series of researches using Tithonia as organic fertilizer to improve soil fertility showed that 136 N Hakim et al: Organic Fertilizer to Control Iron and Commercial Fertilizer Tithonia was able to improve soil fertility by reducing acid content and Al saturation of soil, increased soil pH, soil organic mater content, and soil nutrient of N, P, K, Ca, and Mg levels (Hakim and Agustian 2003;Hakim et al 2006). In addition, Gusnidar (2007) noted that decomposition of Tithonia releases the nutrients of N, P, K, and others and also produce organic acids such as acetic, propionic, salicylic, citric, succinic, and tartaric acid.…”
mentioning
confidence: 99%